Personal Hygiene Health Education to Family Motivation in Performing Self-Care for Mobility Impaired Patients - Andi Nursiah; Idris Idris; Fatmawati Fatmawati; Isymiarni Syarif (Sarana Ilmu Indonesia (salnesia), 2023)
Behavior that is difficult to carry out personal hygiene activities in patients with mobility disorders is caused by limitations in activities that trigger the emergence of less behavior, attention, desire and patient understanding of the importance of carrying out self-care when sick. This study aimed to identify the impact of health education about personal hygiene on family motivation in an effort to carry out self-care for patients with mobility disorders at Laburan Baji General Hospital, Makassar. The research design used was a pre-experimental design with the one group pre-test-posttest design method. The population in this study were all families of patients with mobility impairments in the Baji Kamase treatment room at Laburan Baji General Hospital, Makassar. Samples were drawn using the total sampling technique with a total sample of 84 subjects. Based on the results of the wilcoxon rank test with a significance level of p-value=0,000 was obtained (p-value<0,05). The results of the study showed that there was an influence of health education about personal hygiene on family motivation in carrying out self-care in patients with mobility disorders. Hospitals should provide information media, such as posters about self-care or personal hygiene so that families or visitors can be motivated about the importance of maintaining or caring for personal hygiene.